Candida Glabrata Lymphadenitis Following Infliximab Therapy for Inflammatory Bowel Disease in a Patient With Chronic Granulomatous Disease: Case Report and Literature Review - Lehman, Heather Kristin; Davé, Rahool (Frontiers in Pediatrics, 2021)
Chronic Granulomatous Disease (CGD) is a primary immunodeficiency caused by inactivating genetic mutations in any one of the components of the phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex. Phagocytic cell reactive oxygen species generation is impaired in the absence of a functional NADPH oxidase complex. As a result, patients with CGD are at high risk of developing deep-seated infections with certain bacteria and fungi. Additionally, aberrant inflammation and granuloma formation may occur in multiple organs including the bowels, with inflammatory bowel disease seen as a common inflammatory complication of CGD. Traditionally, TNF-α inhibitors are considered effective biological therapies for moderate-to-severe inflammatory bowel disease. While limited case series and reports of patients with CGD have shown improvement in fistula healing with use of TNF-α inhibitors, several patients have developed severe, even fatal, infections with CGD-related pathogens while on TNF-inhibitor therapy. In this case report, we describe an adolescent male with X-linked CGD and steroid-refractory colitis with perirectal fistula and abscesses, who was initiated on treatment with infliximab, a TNF-α inhibitor. Following his first two infliximab doses, the patient developed a Candida glabrata lymphadenitis and associated ulcerating oropharyngeal lesions, requiring hospitalization and therapy with amphotericin B for resolution. We compare our patient’s case to prior reports of infliximab use in CGD-related inflammatory bowel disease.